Futurism, Territory and War in the Work of Fortunato Depero. (May 2015) - White, Anthony
<x content-type="archive" xml:space="preserve">Abstract</x> The work of the Italian futurist artist Fortunato Depero (1892–1960) conveys the geographic, cultural, and personal dislocation brought about by military conflict. Taking as its subject a series of artworks by the artist from the late 1910s and early 1920s, this article demonstrates how Depero's perception of Trentino – the region in which he was born – was transformed during World War I. As I argue, in works such as La Città meccanizzata dalle ombre, Serrada and Padre e figlio di legno of 1920 Depero explored the radical upending of Italian society, and the profound destabilization of concepts of self, of home and of national identity, that took place as a result of the war.